Successful orthotopic liver transplantation in a patient with a positive SARS‐CoV2 test and acute liver failure secondary to acetaminophen overdose. Issue 3 (23rd October 2020) - Rouphael, Carol; D'Amico, Giuseppe; Ricci, Kristin; Cywinski, Jacek; Miranda, Cyndee; Koval, Christine; Duggal, Abhijit; Quintini, Cristiano; Menon, K. V. Narayanan; Miller, Charles; Modaresi Esfeh, Jamak
Abstract : SARS‐CoV2, first described in December 2019, was declared a pandemic by the World Health Organization in March 2020. Various surgical and medical societies promptly published guidelines, based on expert opinion, on managing patients with COVID‐19, with a consensus to postpone elective surgeries and procedures. We describe the case of an orthotopic liver transplantation (OLT) in a young female who presented with acute liver failure secondary to acetaminophen toxicity to manage abdominal pain and in the setting of a positive SARS‐CoV2 test. Despite a positive test, she had no respiratory symptoms at time of presentation. The positive test was thought to be residual viral load. The patient had a very favorable outcome, likely related to multiple factors including her young age, lack of respiratory COVID‐19 manifestations and plasma exchange peri‐operatively. We recommend a full work‐up for OLT in COVID‐19 patients with uncomplicated disease according to standard of care, with careful interpretation of COVID‐19 testing in patients presenting with conditions requiring urgent or emergent surgery as well as repeat testing even a few days after initial testing, as this could alter management. Abstract : A young patient with a positive SARS‐CoV‐2 test and recent COVID‐19 undergoes successful liver transplantation for acute liver failure secondary to acetaminophen overdose.